Understanding Environment, Social and Governance (ESG) Factors as Path Toward ASEAN Sustainable Finance - Ramadhani, Dita (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
Environment, Social and Governance (ESG) factors are in the trend on todayâ€™s business and financial sector as it finally put sustainability context measurable. ESG has been implemented both on voluntary and mandatory approaches to help financial decision in identifying risk. However, as many countries competing toward full ESG integration, ASEANâ€™s financial institutions are still far from the finish line. According to Paris Agreement, countries were making deal by committing to low-carbon economy and promised Green House Gasses (GHG) emissions cut that consequently forced financial sector to contribute to the target. This paper overlooks into global and ASEAN ESG landscape that impacted ASEAN business and financial sector as whole to raise better understanding on the issue. The result concludes that the dynamics of ESG implementation is a multifaceted situation that ironically put these factors in dispute by business and financial actors. Through ESG strength and weakness, the only way for ASEAN to achieve its promise in international sustainability commitment is by completely transparent and manage their risk as oppose to identify them and report.Â